Should we exploit flexibility of chemical processes for demand response? Differing perspectives on potential benefits and limitations - Svenja Bielefeld; Miloš Cvetković; Andrea Ramírez (Frontiers in Energy Research, 2023)
Electrification of processes and utilities is considered a promising option towards the reduction of greenhouse gas emissions from the chemical industry. Therefore, electricity demand is expected to increase steeply. Since the sources of future low-carbon electricity are variable in nature, there is a need for strategies to match availability and demand. Literature identified the flexibility of chemical processes as one promising strategy to address variability. This study aims to provide insights into how stakeholders from the power sector and the chemical industry consider flexibility in chemical processes and to identify key benefits and bottlenecks. For this article, we combined a review of peer-reviewed and grey literature with stakeholder interviews to map and describe the state of the art of flexible chemicals production, and to identify requirements for further research. The main drivers to investigate the flexibility potential are first, the contribution to energy system reliability, and second, potential cost savings for the industry. Main limitations are considered to be first, the uncertain economic performance of flexible processes due to investment costs, reduced production and uncertain revenues from flexible operation, and second, the complexity of the implementation of flexibility.